ATLAS Run 2 searches for electroweak production of supersymmetric particles interpreted within the pMSSM - Aad, G; Abbott, B; Abeling, K; Barr, AJ; Bortoletto, D; Brückler, TL; Celli, F; Chen, M; Conroy, EI; Cooper-Sarkar, AM; Draguet, MA; Eberwein, GH; et al. (Springer, 2024)
A summary of the constraints from searches performed by the ATLAS collaboration for the electroweak production of charginos and neutralinos is presented. Results from eight separate ATLAS searches are considered, each using 140 fb−1 of proton-proton data at a centre-of-mass energy of √𝑠 = 13 TeV collected at the Large Hadron Collider during its second data-taking run. The results are interpreted in the context of the 19-parameter phenomenological minimal supersymmetric standard model, where R-parity conservation is assumed and the lightest supersymmetric particle is assumed to be the lightest neutralino. Constraints from previous electroweak, flavour and dark matter related measurements are also considered. The results are presented in terms of constraints on supersymmetric particle masses and are compared with limits from simplified models. Also shown is the impact of ATLAS searches on parameters such as the dark matter relic density and the spin-dependent and spin-independent scattering cross-sections targeted by direct dark matter detection experiments. The Higgs boson and Z boson ‘funnel regions’, where a low-mass neutralino would not oversaturate the dark matter relic abundance, are almost completely excluded by the considered constraints. Example spectra for non-excluded supersymmetric models with light charginos and neutralinos are also presented.